2019
DOI: 10.3390/ijms20205201
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus-Associated Hand-Foot and Mouth Disease and Neurological Complications in Japan and the Rest of the World

Abstract: Enteroviruses (EVs) are responsible for extremely large-scale, periodic epidemics in pediatric cohorts, particularly in East and Southeast Asia. Clinical presentation includes a diverse disease spectrum, including hand-foot and mouth disease (HFMD), aseptic meningitis, encephalitis, acute flaccid paralysis, and acute flaccid myelitis. HFMD is predominantly attributable to EV-A types, including the major pathogen EV-A71, and coxsackieviruses, particularly CV-A6, CV-A16, and CV-A10. There have been multiple EV-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 85 publications
(121 reference statements)
2
46
0
1
Order By: Relevance
“…The most frequent complication was myoclonic jerk (61.9%, 306/494), and other common severe complications included aseptic encephalitis (47.0%, 232/494), tachypnea (29.8%, 147/494), vomiting (28.1%, 139/494), tachycardia (24.5%, 121/494), and lethargy (17.0%, 84/494). Gonzalez et al reported that myoclonic jerk is a significant indicator of central nervous system complications in EV-A71-infected HFMD patients [ 17 ], and this was also found in our study. Furthermore, our study showed that myoclonic jerk is also the most frequent complication in severe CVA6 and CVA16-associated HFMD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most frequent complication was myoclonic jerk (61.9%, 306/494), and other common severe complications included aseptic encephalitis (47.0%, 232/494), tachypnea (29.8%, 147/494), vomiting (28.1%, 139/494), tachycardia (24.5%, 121/494), and lethargy (17.0%, 84/494). Gonzalez et al reported that myoclonic jerk is a significant indicator of central nervous system complications in EV-A71-infected HFMD patients [ 17 ], and this was also found in our study. Furthermore, our study showed that myoclonic jerk is also the most frequent complication in severe CVA6 and CVA16-associated HFMD.…”
Section: Discussionsupporting
confidence: 90%
“…Other EV-A types, including CVA2, CVA4, CVA5, CVA6, CVA8, CVA10, CVA14 and CVA16, can also cause severe HFMD [ 3 10 ]. Some members of the species Enterovirus B , such as CVA9, CVB1-5, echovirus 3 (E3), E6, E7 E9, E11, E14, E16, E18, E20, E30 and E33, are also frequently associated with severe complications, especially encephalitis and aseptic meningitis [ 11 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hand, foot, and mouth disease (HFMD) is a common and potentially fatal infectious disease in children under 5 years of age [ 1 ]. Deaths from HFMD occur infrequently [ 2 ], with an annual average of 191 deaths over the past five years in China [ 3 ]. In China, HFMD has caused substantial disease burden, and has remained at the top of the list for Group C infectious diseases in terms of morbidity and mortality since the May 2008 outbreak in Anhui [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surviving cases can suffer long term sequelae [1] . HFMD is caused by human enteroviruses, which are positive-sense single stranded RNA viruses of about 27–30 nm in size [2] . The HFMD etiological agents primarily belong to species of Enterovirus (EV) A, including commonly detected serotypes of EV-A71, coxsackie virus (CV) A16, CV-A6 and CV-A10, as well as other relatively rare serotypes including CV-A4, CV-A2 and CV-A8.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, EV-A71 accounts for the largest proportion of cases with unfavorable clinical outcomes, but the frequency of severe disease caused by other serotypes has been increasing recently [3 , 4] . There are frequent HFMD epidemics in the Asia Pacific region, posing a significant threat to public health [ 2 , 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%